The use of high performance anion exchange chromatography for the detection of counterfeit pharmaceutical products using the excipient content as a marker (Fields)
The aim of the investigation described here was to examine the differences between genuine and counterfeit pharmaceutical products through the development of an analytical method capable of rigorously identifying the sugar-based excipients. High Performance Anion Exchange Chromatography, coupled to Pulsed Amperometric Detection (HPAEC-PAD), supported by Gas Chromatography-Mass Spectrometry (GC-MS), provided a method for the analysis of the carbohydrate based excipients. The analytical method was able to discriminate between the substitution patterns of a number of monosaccharides derived from commonly used excipients and these were compared for both genuine and counterfeit sildenafil citrate based products. The aim of the project was accomplished: the HPAEC-method was employed to analyse a counterfeit pharmaceutical ‘Herbal Viagra’.